‘To sin in loving virtue’: desire and possession in Measure for Measure - Ewan Fernie (Sillages Critiques)
This essay offers a startling new reading of Shakespeare’s Angelo as a paradoxical if not tragic hero who discovers in his sudden and inexorable impulse to rape a nun in the dark that desire is always more-or-less demonic – even, and perhaps especially, when it is most elevated and for what is most sacred and rightly lovable.  The burden of Angelo’s tragic knowledge is that we ‘sin in loving virtue’, that we are more like the carrion than the violet in the sun, that we ‘corrupt with virtuous season’.  Measure for Measure emphasises we cannot but desire as a self and in a body, to the effect that the very otherness we honour in desire we immediately want to compromise by enjoying it for our own.  The paper will argue that though it is Angelo who emblematises this, it is no less true of Isabella; and it is especially depressingly and irredeemably the case with the Duke.